2005
DOI: 10.1172/jci200524405
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial energy metabolism in heart failure: a question of balance

Abstract: "Mitochondrial energy metabolism in heart failure: A question of balance." The Journal of Clinical Investigation. 115,3. 547-555. (2005 The mitochondrion serves a critical role as a platform for energy transduction, signaling, and cell death pathways relevant to common diseases of the myocardium such as heart failure. This review focuses on the molecular regulatory events and downstream effector pathways involved in mitochondrial energy metabolic derangements known to occur during the development of heart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
208
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(228 citation statements)
references
References 121 publications
11
208
0
9
Order By: Relevance
“…Under normal conditions, 60-90% of ATP formation is derived from fatty acid oxidation (FAO) and 10-30% is derived from oxidation of pyruvate, which comes from glycolysis and lactate oxidation in approximately equal amounts. In earlier studies in LVH, we and others have found a shift from FAO to increased rates of glucose oxidation, similar to that in the fetal heart, resulting in an improved cardiac efficiency 13,14 as lower oxygen consumption cost per mole of ATP is generated, compared with FAO. This energy metabolic response may contribute in the long term to adverse consequences on cardiac function owing to diminished energy reserves and a reduced capacity to maintain myocyte lipid balance, as described in children with genetically determined deficiencies in FAO enzymes.…”
Section: Metabolics/energeticssupporting
confidence: 71%
“…Under normal conditions, 60-90% of ATP formation is derived from fatty acid oxidation (FAO) and 10-30% is derived from oxidation of pyruvate, which comes from glycolysis and lactate oxidation in approximately equal amounts. In earlier studies in LVH, we and others have found a shift from FAO to increased rates of glucose oxidation, similar to that in the fetal heart, resulting in an improved cardiac efficiency 13,14 as lower oxygen consumption cost per mole of ATP is generated, compared with FAO. This energy metabolic response may contribute in the long term to adverse consequences on cardiac function owing to diminished energy reserves and a reduced capacity to maintain myocyte lipid balance, as described in children with genetically determined deficiencies in FAO enzymes.…”
Section: Metabolics/energeticssupporting
confidence: 71%
“…Together, these results suggest that mitochondrial function is compromised under hemodynamic stress conditions and exacerbated by the deletion of cardiac Gab1 that could trigger caspase activation and consequent apoptosis of cardiomyocytes and heart failure. 34,35 Mice with cardiac Gab1 deficiency developed spontaneous DCM and heart failure by 3-6 months of age. Mitochondrial dysfunction and mitochondria oxidative stress have linked to age-related heart diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the heart stringently depends on the ATP-generating pathways 37 , and it is therefore enriched in mitochondria. Cardiomyocytes are a good model to study mitochondrial fission because of the abundance of mitochondria.…”
Section: Discussionmentioning
confidence: 99%